(untitled) (Research, Society and Development, 2022)
Histoplasma is a pathogenic fungus that causes histoplasmosis, an endemic systemic mycosis, due to its occurrence in specific regions. Since the first identification of Histoplasma, terminology changes have occurred, initially based on the microscopic characteristics of the infection findings. Subsequently, it remained for a long time divided into varieties within the H. capsulatum (H. capsulatum var. capsulatum, H. capsulatum var. duboisii and H. capsulatum var. farciminosum). The varieties of the species H. capsulatum were differentiated by biological criteria, based on the affected hosts and the pathogenicity/extent of the disease. Later, the advent of advanced molecular biology techniques favored more precise stratifications, with the species being allocated to clades (North America clade 1 - NAm1, North America clade 2 - NAm2, Latin America group A - LAmA, Latin America group B - LAmB, Australia, Netherlands, Eurasian and African). More recently, phylogeny assessments allowed inferences about the existence of 17 species distributed in six groups. The genus Histoplasma is currently described, comprising at least four species (H. capsulatum sensu stricto, H. suramericanim, H. mississippiense and H. ohiense), with the possibility of a fifth genetic group (Africa).